The Dating Service Phenomenon: A Manifestation of Global Culture on Social Media from a Legal and Societal Perspective - Iqlina Ula; Rini Fidiyani (Universitas Negeri Semarang, 2026)
Non-physical virtual dating services have emerged as a rapidly growing socio-digital phenomenon in Indonesia, driven by the post-pandemic acceleration of loneliness and persistent regulatory gaps. This study aims to identify the determinants of the emergence of this phenomenon, examine its existence from the perspectives of law, religion, philosophy, and digital policy, and formulate strategic recommendations based on integrative analysis. This study uses a qualitative method with a juridical-sociological approach with in-depth semi-structured interviews with 12 informants (N=12) through purposive and snowball sampling. This study integrates Rosa's theory of social acceleration, Turkle's paradox of connectivity, Lukacs' reification, and Pound's law as social engineering. The findings identify four synergistic determinants: (1) the acceleration of loneliness exacerbated by the COVID-19 pandemic; (2) the diffusion of the Japanese Rental Kareshi model through digital platforms; (3) the gig economy's economic motives with low entry barriers, including for underage individuals; and (4) regulatory gaps in the ITE Law, the Pornography Law, the National Criminal Code, and the Human Trafficking Law. A multi-perspective review demonstrates the convergence of the four disciplines in assessing this phenomenon as a normatively problematic commodification of intimacy, but divergence in solution orientation. The integrative analysis recommends three systemic responses: the issuance of preventative technical regulations for Komdigi; strengthening the existing legal framework of the ITE Law, the TPKS Law, and the TPPO Law; and platform technical regulations to prevent the algorithmic distribution of content to vulnerable users.